Actuarial Profession and Factor Impacting on the Role of Partly Qualified Actuaries in Insurance Companies of Nepal (Far Western Review, 2023)
Actuarial science is a discipline that assesses financial risks in the field of insurance and finance using mathematical and statistical methods. Actuaries are creative, curious and adaptable human resources and problem solvers, who need to possess different skills and knowledge to solve risk-related problems. Partly Qualified Actuaries (PQA) are semi-professional actuary. They are in the process of studying & appearing for the professional exams, while also garnering work experience & skills in an entry-level Actuary job. From analyzing the financial costs of risk and uncertainty to pricing and reserving, partly qualified actuaries are important in doing the basic to advanced actuarial tasks in these businesses. The research paper investigates the role of partly qualified actuaries in the insurance industry in Nepal and analyzes the factors impacting the role of PQA in Nepalese insurance companies. Basically, this research paper investigates the role of partly qualified actuary in Nepal and to studies the scenario of partly qualified actuary in Nepal. The research uses qualitative and quantitative data collected from PQA, insurance companies’ staffs, policy makers and some academicians of Nepal who are well informed about actuary. The research shows that the number of PQA is increasing in Nepal every year and they are working in different insurance companies. The study shows that Partly Qualified Actuaries can reduce the need for foreign actuaries in Nepal.